The Correlation and Relationship Between Diameter Increment and Climatic Elements in a Secondary Forest of Universiti Malaysia Sarawak, Malaysia - Karyati, K.; Isa, Ipor; Ismail, Jusoh; Mohd Effendi, Wasli (Atlantis Press International B.V., 2022)
Climatic elements play important roles in the growth of plants. The aims of this study were to determine correlation and relationship between plant growth and climatic elements (rainfall, rainy days, temperature, relative humidity, and solar radiation) in a secondary forest of Universiti Malaysia Sarawak (Unimas), Sarawak, Malaysia. The plant growth was indicated by diameter at breast height (DBH) of some selected tree species. The DBH increment of 30 selected trees which consisted of nine species (Acacia mangium, Cratoxylum arborescens, Cratoxylum glaucum, Endospermum diadenum, Euodia glabra, Macaranga gigantea, Macaranga triloba, Vernonia arborea, and Vitex pubescens) was recorded monthly through the use of Series 5 Manual Band Dendrometer for a period of 1 year. The result showed that increments of several selected species were positively and negatively correlated to one or more climatic elements. The relationship between DBH increment of E. diadenum and climate elements were significant.